Correlation between Family Support and Quality of Life Among Post-Stroke Patients - Thomas Wibowo; Wantasya Febriani (Yayasan Ahmad Mansyur Nasirah, 2026)
Stroke is one of the leading causes of disability that can reduce patients’ quality of life. Post-stroke patients often experience physical, psychological, and social limitations, thereby requiring family support to manage their daily lives. Family support plays a crucial role in assisting the care process, rehabilitation, and patients’ adaptation to post-stroke conditions. This study aimed to determine the relationship between family support and quality of life among post-stroke patients. This research design uses a quantitative research approach. The approach method taken is a cross-sectional approach with analysis using Spearman’s rank. The study results, with a p-value of 0.001 < 0.05, showed that there was a relationship between family support and quality of life among post-stroke patients. The correlation coefficient (r = 0.712) indicated a strong positive relationship, suggesting that greater family support is associated with improved quality of life. In conclusion, according to the findings of this study, there is a correlation between family support and quality of life among post-stroke patients. A recommendation of the research is that family support can be used to help post-stroke patients with medication.